The Effect of Intellectual Capital, Corporate Social Responsibility Disclosure and Environmental Performance on Financial Performance Case Study of State-Owned Enterprises Listed on the Indonesia Stock Exchange in the Period 2021-2023 - Purba, Livia Grestallia; Simanjuntak, Arthur; Elisabeth, Duma Megaria (Future Science, 2025)
The aim of this study is to investigate how intellectual capital, CSR, and environmental performance affect the financial performance of an organization. This research uses data from company websites, BEI, and Keme The independent variables used are the company's financial performance, as measured by ROA and ROE. Other independent variables are Intelctual capital, as measured by VAICTM, corporate social responsibility disclosure, as measured by CSRIj, and environmental performance, as measured by PROPER. The purposive sampling method produced 51 company data as research samples. Hypothesis testing using multiple regression analysis. This study processed the data with Microsoft Excel and tested with SPSS 25. The results showed that intellectual population, CSR disclosure, and environmental performance affect financial performance.